2023
DOI: 10.7759/cureus.35094
|View full text |Cite
|
Sign up to set email alerts
|

Selective Androgen Receptor Modulators (SARMs)-Induced Liver Injury: A Case Report and Review of Literature

Abstract: Drug-induced liver injury (DILI) is one of the leading causes of death from acute liver failure (ALF) in the United States, accounting for approximately 13% of ALF cases in the United States. Selective androgen receptor modulators (SARMs) were first developed to increase muscle mass while avoiding the side effects of conventional androgenic steroids. Although not Food and Drug Administration (FDA) approved, they are widely available online and are consumed to enhance athletic performance. We report a 22-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Three patients in our series had testing of the SARM used which confirmed the presence of the labelled SARM and in one product there was an additional SARM identified. Less than 20 cases of DILI due to SARMs have been reported in the literature since 2020 involving ligandrol (LGD‐4033), testolone (RAD‐140), ostarine (enobosarm) and YK‐11 6–9,16,17 . We found a similar demographic of patients with DILI due to SARMs, namely all males, aged 24–46 years (other cases were 19–52 years).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Three patients in our series had testing of the SARM used which confirmed the presence of the labelled SARM and in one product there was an additional SARM identified. Less than 20 cases of DILI due to SARMs have been reported in the literature since 2020 involving ligandrol (LGD‐4033), testolone (RAD‐140), ostarine (enobosarm) and YK‐11 6–9,16,17 . We found a similar demographic of patients with DILI due to SARMs, namely all males, aged 24–46 years (other cases were 19–52 years).…”
Section: Discussionsupporting
confidence: 59%
“…Less than 20 cases of DILI due to SARMs have been reported in the literature since 2020 involving ligandrol (LGD-4033), testolone (RAD-140), ostarine (enobosarm) and YK-11. [6][7][8][9]16,17 We found a similar demographic of patients with DILI due to SARMs, namely all males, aged 24-46 years (other cases were 19-52 years). We found 86% to be symptomatic, whereas all previously reported cases were.…”
Section: Selective Androgen Receptor Modulatorssupporting
confidence: 58%
“…peak 73 IU/L); TB 0.8 mg/dL Negative No No medical history Not mentioned Arayangkool et al [ 46 ] LGD-4033 Ostarine RAD-140 Jaundice Pruritus Weight loss Abdominal pain Cholestatic liver injury Canalicular bile plugs Hepatocellular dropout Acute tubular injury with pigmented bile casts 8 weeks No AST 52 IU/L ALT 52 IU/L ALP 343 IU/L TB 43.3 mg/dL Negative No No medical history Analytical testing for SARMS not performed. Dose was not specified Reported biopsy Ladna et al [ 47 ] RAD-140 Nausea, vomiting, severe right upper quadrant abdominal pain, jaundice, dark urine, constipation Acute liver injury 8 weeks No AST 51 IU/L ALT 243 IU/L TB 4.9 mg/dL Negative No No medical history Analytical testing for SARMS not performed Mohamed et al [ 48 ] RAD-140 Jaundice, nausea, fatigue, dark urine, acholic light gray-colored stool, pruritus Mixed portal hepatitis, cholestasis, biliary reactive changes 16 weeks Performance-enhancing supplement AST 70.8 IU/L (1.18 µkat/L) ALT 99.6 IU/L (1.66 µkat/L) ALP 318 IU/L (5.3 µkat/L) TB 427.5 mg/dL Negative No No medical history Analytical testing for SARMS not performed. Dose was not specified Reported biopsy Cardaci et al [ 49 ] LGD-4033 10 mg daily Controlled study—not reported Controlled study—not reported 5 weeks …”
Section: Resultsmentioning
confidence: 99%
“…The duration of SARM use in reported cases ranged from 2 to 12 weeks before developing symptoms, which was consistent with our patient who took them for 2 months. 3 Given that cholestatic liver injury patterns have been reported as a characteristic of SARM-associated DILI, 4 providers and athletes need to recognize the danger of SARMs, which include the potential to cause liver and kidney injury.…”
Section: Discussionmentioning
confidence: 99%